The leadership solution - Shaffer, James C. (McGraw Hill, 2000)
Everyone communicates, problem is, most don't have the necessary skills to communicate effectively. The Leadership Solution offers six steps for developing better leadership communication skills to improve performance. Using lively anecdotes and real-world examples, Jim Shaffer provides firsthand accounts of how Towers Perrin has helped dozens of Fortune 500 companies to fully engage their employees, and consistently keep the company's strategies and goals in mind. Far from a gimmick or method du jour, The Leadership Solution is a complete program designed to focus employees on achieving valuable, measurable business results. It features: Twenty ways to connect people to strategy now. Three communication sources that most influence action. Nine guidelines for negotiating through a merger or acquisition.